2021
DOI: 10.1111/jfb.14971
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive dynamics of the invasive lionfish (Pterois miles) in the Eastern Mediterranean Sea

Abstract: The lionfish Pterois miles invaded the Mediterranean Sea in 2012 and spread fast to the entire eastern basin. This study provides evidence of successful spawning and the first detailed analysis of P. miles ovarian dynamics in the Mediterranean Sea. The ovarian reproductive phases of mature females collected from Cyprus (eastern Mediterranean) between September 2017 and August 2018 were analysed, both macroscopically and histologically. The results suggested a prolonged oocyte recruitment and development season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…According to a recent study [46], reproduction in Cyprus occurs in the summer. Mouchlianitis et al (2021) [124] are the only researchers that examined all aspects of P. miles reproductive biology in the eastern Mediterranean. These authors reported that the species exhibited active spawning only in June and July, but females capable of spawning were present throughout autumn.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent study [46], reproduction in Cyprus occurs in the summer. Mouchlianitis et al (2021) [124] are the only researchers that examined all aspects of P. miles reproductive biology in the eastern Mediterranean. These authors reported that the species exhibited active spawning only in June and July, but females capable of spawning were present throughout autumn.…”
Section: Discussionmentioning
confidence: 99%
“…At Samos, only five species were the most abundant, C. chromis (18.46%), Sarpa salpa (Linnaeus, 1758) (11.6%), S.cretense (8.47%) Coris julis (Linnaeus, 1758) (7.33%) and S. rivulatus (6.56%), in total 52.42%. Table 6 presents the total contribution of most abundant species (14) for Samos sites. Finally, at Santorini the most frequent species were C. chromis (22.06%), S. luridus (10.21%), S. rivulatus (10.21%), D. sargus (6.97%) and S. maena (5.27%), totally 54.72%.…”
Section: Plos Onementioning
confidence: 99%
“…In Mediterranean waters, lionfishes showed an extend period of reproduction, that seems to peak during the summer. Moreover, each female is able to complete its reproduction cycle multiple times during each season [14]. Several studies documented that its feeding behaviour and diet habits can set significant alterations on regional food webs in the Mediterranean basin [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the impacts of lionfish in the Mediterranean, the European Commission funded the project ‘Preventing a LIONfish invasion in the MEDiterranean through early response and targeted Removal ‐ RELIONMED’ (LIFE16 NAT/CY/000832) that aimed to make Cyprus the first line of defence against the invasion (Kleitou et al, 2021a). After a year of research efforts to study its biological and ecological characteristics (Mouchlianitis et al, 2022; Savva et al, 2020), it became clear that lionfish adapted to the local conditions and quickly established growing populations that spread widely. A population suppression approach was adopted, also known as functional eradication (Green & Grosholz, 2021).…”
Section: Introductionmentioning
confidence: 99%